Android Based Light Control System Using Arduino - Yuda Irawan; Achmad Deddy Kurniawan; Refni Wahyuni; Naima Belarbi; Mbunwe Muncho Josephine (Journal of Telecommunication Control and Intelligent System, 2021)
Abstract— PT. Asuransi Bangun Askrida has many rooms where each room has lighting in every room. The lighting uses a lot of lights using a switch in every lamp and. Of course it will take a lot of time to control the room lights if you still use the manual method. In addition, manual switch control cannot save electrical energy. We only need to use electricity when needed. But sometimes it is this small thing that is often neglected by the company or its employees. For example, the room lights, companies or employees sometimes neglect to turn off the room lights, even though they are not in the room and sometimes the room is locked by the manager who has important documents. Based on these problems, the researchers are interested in designing and building a room light control system at PT. Asuransi Bangun Askrida which allows to control these lights using a smartphone. With the existence of a light control system at PT. ASURANSI BANGUN ASKRIDA based on android, it can make it easier for security officers to control lights from an ideal distance. Room light control system that has been tested and is running well.